A Shift of Typology the Nuro’ulama’ KE PA PE’SSE’AN: Voter Typology Study of Madura Pandalungan Society in the 2019 Simultaneous Elections in Bondowoso Regency - Darsono, Darsono; Pujileksono, Sugeng; Anam, Hairul; Syakur, Abd (Yayasan Sembilan Pemuda Indonesia, 2023)
Democracy which is synonymous with the exercise of power from the people, by the people, and for the people is realized by electing representatives of the people through general elections for members of the DPR, DPD, President and Vice President, and Provincial and Regency/City DPRD. For political purposes, it is known that there are typologies or characteristics of voters and these typologies are important in winning election contests. This study aims to identify the typological characteristics of the Madurese Pandalungan voters in the 2019 simultaneous elections in Bondowoso Regency as well as to obtain scientific information on the factors that influence them. The method used in this research is descriptive. The results of this study found that (1) The typology of Madurese Pandalungan voters in the 2019 simultaneous elections in Bondowoso Regency consisted of (a) typology of penter voters, (b) typology of nuro’ ulama’ voters, (c) typology of focal voters, (d) typology of ta’ro’nuro’ voters, and (e) typology of pa pe’sse’an. The domination of the nuro’ulama’ typology is greater, but there is a shift in typology from the nuro’ulama’ typology to the pa pe’sse’an voter typology. (2) The typology is influenced by factors (a) voter characteristics with variables of socio-cultural conditions and value systems, educational and economic factors, and kinship or family factors, (b) mass media factors, (c) characteristics of political parties and legislative candidates, and (d) amae’n pe’sse’ factors.